A family of Zn(ii)/Cd(ii) halide systems incorporating 5, 5′-di(pyridin-2-yl)-3, 3′-bi(1, 2, 4-triazole). Issue 6 (15th January 2016) - Yao, Peng-Fei; Liu, Han-Fu; Huang, Fu-Ping; Feng, Fang-lin; Qin, Xiao-Huan; Huang, Mei-Li; Yu, Qing; Bian, He-Dong
Abstract : By using 5, 5′-di(pyridin-2-yl)-3, 3′-bi(1, 2, 4-triazole) (2, 2′-H2 dbpt) as a building block, six novel coordination complexes based on the M(ii )/X (M = Zn, Cd; X = Cl, Br, I) system were generated. Abstract : By using 5, 5′-di(pyridin-2-yl)-3, 3′-bi(1, 2, 4-triazole) (2, 2′-H2 dbpt) as a building block, six new coordination complexes: Zn3 (2, 2′-Hdbpt)2 (H2 O)Cl4 (1 ), [Zn2 (2, 2′-dbpt)Cl3 ]·Et3 NH n (2 ), [Cd3 Cl3 (2, 2′-dbpt)3 ]·2H2 O n (3 ), [Cd3 I3 (2, 2′-dbpt)3 ]·H2 O n (4 ), [Cd2 Br2 (2, 2′-dbpt)]·H2 O n (5 ), and [Cd2 I4 (2, 2′-H2 dbpt)] n (6 ), based on the M(ii )/X (M = Zn, Cd; X = Cl, Br, I) system were generated.1 and2 bear a Zn3 supermolecule and a 1D wave-like chain, respectively.3 and4 are isostructural, giving a new 3D architecture with a (4 12 ·6 3 ) topology based on the [Cd6 ] ring as a node bridged by the μ2 -Cl − ion and the μ2 -I − ion, respectively.5 is a 2D framework with a (3 2 ·6 2 ·7 2 ) topology based on the [Cd4 ] subunit.6 reveals a 1D modified trapezoid chain with a (4 2 ·6) topology based on the trans -bridging 2, 2′-H2 dbpt. Based on the interesting structural results, the solid-state luminescence properties of complexes1–6 were investigated, which revealed that the emission maximum wavelengths can be tuned in a large range of 403–498 nm. These results indicate that 2, 2′-H2 dbpt is not only an excellent building block to construct coordination complexes with interesting structures but also a good precursor to construct potential photoactive materials.